ISLAMIC INHERITANCE SYSTEMATICS IN THE CITY OF BINJAI (CASE STUDY OF THE DIVISION OF INHERITANCE OF DAUGHTER AND BIOLOGICAL UNCLE) - Adliya Muchni Muharrama; Hasan Matsum; Muhammad Syukri Albani Nasution (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2020)
The problem of inheritance that is often a problem in society is when a deceased leaves only daughters so that the father's brother gets the inheritance because there is no barrier to inheritance. In general, the deceased's wife and daughter are not willing to leave the inherited property due to the role of the father's biological brother as long as the deceased (father) does not play a maximum role as guardian. However, if the biological uncle's share is not given, it is feared that there will be damage to the family relationship between the biological uncle and the deceased daughter. So later, in Binjai City, the biological uncle was still given the inheritance, but only part of the actual portion. This study analyzes the practice of inheritance settlement between uncles and daughters in the Binjai City community and the legal arguments of religious leaders who play a role in it. The research method used is field-qualitative with a normative approach and legal sociology. This research found that in solving the distribution of inheritance between daughters when dealing with paternal brothers in Binjai City, there are generally two ways of settlement, namely: First, the clergy want to remain consistent in applying the provisions of inheritance law by traditional fiqh, namely the father's biological brother gets the share of the heir when dealing with an only daughter. Second, scholars try to update the meaning of Islamic inheritance law by placing the position that a daughter can wear the hijab from her father's brotherMasalah waris yang kerap menjadi persoalan di tengah masyarakat adalah ketika mayit hanya meninggalkan anak perempuan, sehingga saudara laki-laki dari pihak ayah mendapatkan harta warisan disebabkan tidak terdapat penghalang waris. umumnya pihak isteri si mayit dan anak perempuannya tidak rela harta warisan keluar dari rumah disebabkan peran saudara laki-laki kandung pihak ayah selama si mayit (ayah) tidak berperan maksimal sebagai wali. Namun jika bagian paman kandung tidak diberikan, dikhawatirkan terjadi rusaknya hubungan keluarga antara paman kandung dengan anak perempuan mayit. Maka kemudian di Kota Binjai, paman kandung masih diberi harta warisan namun hanya sebagian dari bagian sebenarnya. Penelitian ini menganalisis praktik penyelesaian kewarisan antara paman dan anak perempuan pada masyarakat Kota Binjai dan argumentasi hukum tokoh agama yang berperan di dalamnya. Metode penelitian yang digunakan adalah kualitatif-lapangan dengan pendekatan normatif dan sosiologi hukum. Penelitian ini menemukan bahwa penyelesaian pembagian waris antara anak perempuan disaat berhadapan dengan saudara laki-laki dari pihak ayah di Kota Binjai, umumnya terdapat dua cara penyelesaian, yaitu: Pertama, ulama ingin tetap konsisten menerapkan ketentuan hukum waris sesuai dengan fikih tradisonal yaitu saudara laki-laki kandung dari pihak ayah mendapatkan bagian dari ahli waris ketika berhadapan dengan anak perempuan tunggal. Kedua, ulama mencoba memperbarui makna hukum kewarisan Islam itu sendiri dengan menempatkan posisi anak perempuan dapat menghijab saudara laki-laki dari pihak ayah